Socioeconomic Development of Regions of Siberia and Russian Far East: Statistical Analysis - Dashanimaevich Tsyrenov, Dashi; ., .; ., . (International Journal of Engineering and Technology, 2018)
The economic development of Russia, given the countryâ€™s vast territory, the distribution patterns of natural resources and population, and the diverse climate conditions, is logically uneven and characterized by territorial variation. Particular focus of the federal government should be placed on the conditions emerging in Siberia and the Russian Far East. The major limiting factor is the increasing population outflows to the central federal subjects of the Russian Federation, particularly visible among the working-age population. Apart from it, another limiting factor is the natural conditions in these two federal districts, namely, the harsh weather conditions, the typical inland climate, seismic activity, etc. Moreover, a major part of Siberia and the Far East is designated as a territory with special requirements in terms of natural resource development, which is due to the existing national reserves and parks. The Baikal natural area, the basin of Lake Baikal, are of particular importance. These factors have brought to the foreground the need for a break-up of the Siberia Federal District and the Far East Federal District to improve the economic efficiency of such spacious areas of the country. There is a proposal to establish a new federal district known under the working reference as â€œCentral Eurasiaâ€ and meant to include the Republics of Buryatia, Tyva, Khakassia, and Sakha (Yakutia), the Trans-Baikal and Krasnoyarsk Territories and the Irkutsk region. The proposed spatial arrangement of productive forces would improve the efficiency of use of both labor and natural resources.Â
Keywords: Federal District; Spatial Arrangement; Siberia; Far East; Eurasian Territory; Interregional Cooperation.